2012
DOI: 10.1002/9781118307397
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods for Food and Dairy Powders

Abstract: Determining the dry matter is an essential measure with regard to food powders because:. it gives the dry matter content of the product, which can then be used to determine the material cost and commercial value of the powder . it gives the moisture (or water content) of the product, which is the difference between 100% total weight and the dry matter content. The dry matter content directly relates to the amount of water in a product. This in turn can be used to determine availability (water activity; cf. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 0 publications
6
107
0
24
Order By: Relevance
“…For a given evaporation capacity, the decrease in the outlet air 307 temperature in spray-drying is linked to an increase in its relative humidity. This results in an 308 significant increase in the powder moisture content, as its water activity tends to equilibrate with 309 air relative humidity (Schuck et al, 2012). Incubation of the protein concentrate with the 310 chymosin did not significantly influence the moisture content values as shown in Table 2.…”
Section: Powder Physicochemical Properties 300mentioning
confidence: 86%
“…For a given evaporation capacity, the decrease in the outlet air 307 temperature in spray-drying is linked to an increase in its relative humidity. This results in an 308 significant increase in the powder moisture content, as its water activity tends to equilibrate with 309 air relative humidity (Schuck et al, 2012). Incubation of the protein concentrate with the 310 chymosin did not significantly influence the moisture content values as shown in Table 2.…”
Section: Powder Physicochemical Properties 300mentioning
confidence: 86%
“…On the other hand, the reduction of bulk density might be due to the enlargement of particle size and/or reduction of moisture content. As also stated by Schuck, Jeantet, and Dolivet (2012), the bulk density and porosity of powder are highly affected by the particle size of powder and its moisture content, amount of air occluded in each particle, interstital air between particles and absolute density of powder.…”
Section: Bulk Densitymentioning
confidence: 99%
“…To ensure good resuspension of the powder, the suspension was stirred at 900 rpm for 6 h at 40°C in a water bath and then for 16 hours at room temperature. The rehydration of the casein micelle powder was checked by laser light diffraction as defined by Schuck, Dolivet, & Jeantet (2012). The results expressed in volume showed that more than 90 % of the particles were of size of casein micelles (150 induced by classical dialysis against pure water.…”
Section: Preparation Of Different Ca Suspensionsmentioning
confidence: 99%